Effect of number of birds per cage on poultry behaviour - Dalibor Klecker; Ladislav Zeman (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2004)
The aim of this ethological experiment was to study the effect of decreasing numbers of hens kept in cages on changes in their behaviour. The numbers of hens were reduced from three to two and one bird per cage and the results of ethological observations were as follows: in cages with three birds the behaviour of hens was relatively normal and corresponded with behaviour patterns observed in cage technologies. A reduction to two hens per cage increased their fighting activities because one of them struggled for a dominant position so that the performance of subordinated hen was usually decreased. Individual rearing resulted in attenuated feeding activities, reduction of motivation behaviour.